Report into the loss of the SS Titanic : a centennial reappraisal /: a centennial reappraisal. (2016) - Halpern, Samuel; Akers-Jordan, Cathy; Behe, George; Beveridge, Bruce; Chirnside, Mark; Fitch, Tad; Gittins, Dave; Hall, Steve; Mitcham, Lester J; Weeks, Capt Charles; Wormstedt, Bill
No abstract available